Problematika Pembelajaran Bahasa Arab di Madrasah Ibtidaiyah Negeri 1 Medan - Samsul Haq; Annisa Annisa; Arjuna Dwi Maulana; Mutia Zahara (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
Learning is the activity of educators and students in transferring knowledge and absorbing knowledge, and learning has the ultimate goal, namely that teachers hope that students will gain useful knowledge in the classroom and have good character after receiving a series of lessons. Learning still focuses on increasing students' understanding gained from the presentation of the material and the teacher's explanations. However, it turns out that learning still cannot be avoided from problems, especially in the field of foreign languages, both experienced by teachers and students. Therefore, researchers focus on discussing problems in learning Arabic. Researchers took the location and samples from Madrasah Ibtidaiyah (MI) Negeri 1 Medan. This research was conducted using qualitative methods by conducting field observations. The researcher's aim is to get points that are problematic in learning Arabic in MI so that they can be used as a reference for educators or prospective educators in finding solutions in the future. The problems that exist in this school are that it is difficult for students to control their emotions considering that they are still children, then when teaching educators only use one method, namely the lecture method, the language they have mastered is minimal, the facilities and media for teaching are lacking. adequate, and the use of Arabic is only applied in class.